Clinical review of two fatal equine cases of infection with the insectivorous bat strain of Australian bat lyssavirus. Issue 9 (September 2014) - Annand, EJ; Reid, PA
<x xml:space="preserve">Abstract</x> Case series The first two confirmed cases of Australian bat lyssavirus (ABLV) infection in horses are presented. Both cases occurred in the same week in May 2013 in paddock mates in south‐east Queensland. Australia has been one of only a few countries considered free from rabies‐like viruses in domestic animal species. ABLV infection had previously only been confirmed in bats and humans. All three confirmed human cases were fatal, the latest in February 2013. An additional human case of possible abortive infection in 1996 has also been reported. Both equine cases reported here resulted in euthanasia. The risks of infection across other mammalian species are still to be determined. Conclusions These two equine cases highlight that ABLV should be considered as a differential diagnosis in animals with similar clinical presentations in Australia. There is a need for greater awareness regarding the zoonotic risk, use of personal protective equipment, pre‐ and post‐exposure prophylactic measures and laboratory diagnostic options. The authors recommend ABLV testing for all Australian cases of progressive equine neurological disease.